2021
DOI: 10.1042/etls20210245
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the central nervous system: tissue engineering of the cellular microenvironment

Abstract: With the increasing prevalence of neurodegenerative diseases, improved models of the central nervous system (CNS) will improve our understanding of neurophysiology and pathogenesis, whilst enabling exploration of novel therapeutics. Studies of brain physiology have largely been carried out using in vivo models, ex vivo brain slices or primary cell culture from rodents. Whilst these models have provided great insight into complex interactions between brain cell types, key differences remain between human and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Regeneration of defective neurons in central nervous system is a highlighted issue for neurodegenerative disease treatment [1]. Various tissue engineering approaches have focused on neuritogenesis to achieve the regeneration of damaged neuronal cells because damaged neurons often fail to achieve spontaneous restoration of neonatal neurites [2].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Regeneration of defective neurons in central nervous system is a highlighted issue for neurodegenerative disease treatment [1]. Various tissue engineering approaches have focused on neuritogenesis to achieve the regeneration of damaged neuronal cells because damaged neurons often fail to achieve spontaneous restoration of neonatal neurites [2].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Traditional 2D cultures with Petri dishes were reductionist approaches, unable to explain the possible mechanisms and effectually predict clinical outcomes in humans. New biomaterials, such as hydrogels, have provided a versatile and tunable alternative ( Walczak et al, 2021 ). It has a high water content and porous structure, which shows similar mechanical and biological properties as ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanical properties of biomaterials in neuron culture have not been fully understood, they are undoubtedly an important issue, and novel models could be developed based on the principle of regulating such properties ( Walczak et al, 2021 ). This review explores the novel in vitro models with primary neurons developed in recent years, from the 2D in vitro model, ex vivo culture, and spheroid to 3D cultures as a scaffold, 3D bioprinting, and on-chip culture, especially focusing on the design and application of those models, and the new biomaterials involved ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering has advantages in this field since it strives to enhance regeneration and provides longer-lasting or even permanent vocal fold augmentation [ 5 , 6 ]. Tissue engineering has been researched extensively in several regenerative techniques, including cartilage, neuron, cardiac, and bone regeneration [ 7 , 8 , 9 , 10 ]. Nonetheless, previous studies [ 11 , 12 , 13 , 14 ] have identified vocal fold fibroblasts, muscle progenitor cells, embryonic stem cells (ESCs), bone marrow mesenchymal stem cells (BMMSCs), and adipose stem cells (ASCs) with or without the use of a scaffold as a delivery vehicle for vocal fold regeneration.…”
Section: Introductionmentioning
confidence: 99%